Remarkable new Australian mothflies (Diptera, Psychodidae) - Wagner, Rüdiger (Zootaxa, 2018)
Queenslandomyia cannula gen. nov. et sp. nov. from Queensland, and Theischingerus imbricatus gen. nov. et sp. nov. (Diptera, Psychodidae) from New South Wales, are described and figured. Queenslandomyia is characterized by the shape of the basal 4 flagellomeres with digitate lateral extensions, and an afferent sclerotized thin channel to flagellomere 4; parameres connate to a large central sclerite with apical setae. Theischingerus is conspicuous by the unusual furcation of the Radius sector vein in R2 and R3+4 so that between radial and medial forks only a single vein (R5) occurs. Rotundopteryx notata (Duckhouse, 1966) is redescribed and the genus diagnosis of Rotundopteryx Duckhouse 1990 is expanded, based on a remarkable connection of the basiphallus, with the distiphallus and the parameres, and of the subepandrial plate with the surstyli and the hypoproct. Records of other 6 species are provided.